Handbook of nutrient requirements of finfish (CRC Press, 1991)
This book provides a summary of qualitative and quantitative nutrient requirements for almost all cultured finfish for which a significant amount of nutritional information now exists. Information is presented by species and includes how each species is cultured, an index of production, regional locations where each species is being cultured, examples of purified or test diets and special conditions required for laboratory studies, nutrient requirements and practical diet formulation. Discussions of special diets and feeding practices are included for certain species. This book will be a useful guide for students, researchers, practicing nutritionists, aquaculturists, and feed manufacturers interested in fish nutrition.